(untitled) (PROCEEDING OF INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDY, 2025)
This research aims to develop a STEM (Science, Technology, Engineering, and Mathematics) based Natural Sciences (IPA) textbook that is appropriate to the maritime context. In the context of education in coastal or maritime areas, science learning needs to be adapted to the characteristics of the surrounding environment, such as marine ecosystems, natural resources, as well as the challenges and potential that exist in maritime areas. The textbook being developed is expected to increase students’ understanding of science concepts through an interdisciplinary approach that integrates science, technology, engineering and mathematics. The type of research applied to achieve the research objectives is qualitative research with a descriptive/documentary interview, case study/exploratory approach. The research results show that the developed STEM-based junior high school science textbook is able to improve students’ critical thinking and problem solving skills, as well as providing a deeper understanding of local maritime issues. This textbook also succeeds in encouraging students’ active involvement in STEM-based experiments and projects that are relevant to everyday life in coastal areas. Overall, the development of this textbook can be an innovative alternative in enriching the junior high school science curriculum in the maritime area, as well as preparing the younger generation who are ready to face global challenges through a contextual and applicable science approach.